Strategi Brand Positioning Partai Persatuan Pembangunan dalam Menciptakan Identitas Publik di Kabupaten Deli Serdang - Zailanty, Sabrina; Tanjung, Muaz (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the brand positioning strategy of the United Development Party (PPP) in Deli Serdang Regency in shaping public identity and to identify the factors influencing the effectiveness of the strategy. The research employs a qualitative approach with a descriptive method through interviews, observation, and documentation. The findings indicate that the brand positioning strategy is built through the reinforcement of Islamic ideology as the party’s core identity, reflected in its organizational structure, religious activities, and religion-based welfare programs. The consistency of ideological values and direct involvement in socio-religious activities strengthen the party’s image as a firm Islamic political organization that is close to the community and actively engaged in religious life. This differentiation enables the public to easily recognize the party’s character and enhances public trust. The effectiveness of the strategy is influenced by external factors such as low public trust in political parties and internal factors including organizational solidarity and adaptability to local political dynamics. Socially oriented and religious value-based communication strategies are proven to strengthen legitimacy, voter loyalty, and the party’s competitiveness at the local level.